Agricultural growth and its impact on gross state value added: An econometric analysis of major crop sectors in Haryana - KUMAR, AJAY; TIYNDEL, G JOHNS; SAGWAL, ARADHANA; SIHAG, PARVEEN; KUMAR, DINESH; MANISHA; KUMAR, VINAY; SUSHMA; CHAHAL, SUNIL; PARDEEP (The Indian Journal of Agricultural Sciences, 2025)
Agriculture remains a vital primary sector in Haryana and contributes significantly to both the state’s economy as well as India’s food security. The basic objective of the research was to investigate the relationship between the Gross State Value Added (GSVA) and the output of major agricultural sub-sectors (cereals, pulses, and oilseeds) in Haryana by using an econometric analysis. The study aimed to analyze how changes in the output of key agricultural sectors have impacted the GSVA of the state over the period of 30 years from 1993–94 to 2022–23. The time series data were collected from various issues of the state statistical abstract of Haryana and other government publications related to the objective of the study. Data were analyzed by using the ordinary least square method and the Augmented Dickey Fuller test. The results revealed that output from two sectors (cereals and oilseeds) has a positive and significant relationship with GSVA, whereas pulses have exhibited a negative relationship. Therefore, the study suggested that the Government of Haryana should strengthen their policies and support for cereal and oilseed production and address challenges in the pulse sector for better contribution and agricultural growth in future.